Marketing Research and Social Responsibility: Ethical Obligations toward the Society - Sami Alsmadi (Journal of Accounting, Business and Management (JABM), 2010)
The objective of this article is to examine ethical behavior of marketing researchers and social responsibility, focusing on researchers moral responsibilities toward the society. The article looks at social responsibility from several perspectives (for example, Windsor, 2006, Kerin et al, 2009, Porter and Kramer, 2006). The analysis highlights the interaction between research suppliers and sponsoring clients (users of business research) in most marketing research, focusing on researchers ethical obligations in view of the various demands and pressures exerted by some sponsoring clients. The conclusions emphasize the importance of ethical integrity and social responsibility of researchers and stress the need to improve ethical standards relating to corporate social responsibility in marketing research. Relevant legal and regulatory issues are also considered in the context of ethical research.